2004
DOI: 10.1111/j.1755-6686.2004.tb00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain Degree and Skin Damage During Arterio‐venous Fistula Puncture

Abstract: K e Y W o r d s • Vascular access • Arteriovenous fistula • Puncture pain • Fistula damage • Needle bevel position B i o d a t a Rodolfo Crespo has worked in renal care since 1981 and was appointed Chief of Renal Nurse Staff at the Chronic Dialysis Unit in 1987. He has been a Lecturer in Medical Nursing at the University of Córdoba since 1990. His research activity is focused on vascular access of the renal failure patient and work related to nurse management.The aims of this study were to evaluate the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 5 publications
1
29
0
Order By: Relevance
“…The studies included in the review were published between 2004 and 2019. 8,[12][13][14][15][16][17]19,20,22,24,[26][27][28]30,[32][33][34][40][41][42]44 The reviewed literature indicated that the majority of patients being dialyzed using arteriovenous fistulas or grafts reported a moderate degree of cannulation pain. The designs of the selected studies were randomized controlled trials (n = 14; 40%), 5,10,18,21,23,25,[29][30][31][35][36][37][38][39] and observational studies (n = 21; 60%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies included in the review were published between 2004 and 2019. 8,[12][13][14][15][16][17]19,20,22,24,[26][27][28]30,[32][33][34][40][41][42]44 The reviewed literature indicated that the majority of patients being dialyzed using arteriovenous fistulas or grafts reported a moderate degree of cannulation pain. The designs of the selected studies were randomized controlled trials (n = 14; 40%), 5,10,18,21,23,25,[29][30][31][35][36][37][38][39] and observational studies (n = 21; 60%).…”
Section: Resultsmentioning
confidence: 99%
“…No studies were found prior to 2004. In 66% (n = 23) of the reviewed articles a visual analog scale (VAS) was used to assess pain, 5,8,10,12,[14][15][16][17][18][19][20][21][22][23]30,32,34,[36][37][38][39]42,44 while in 22% (n = 8) a numerical rating scale (NRS) was used 13,24,25,29,31,35,40,41 ; three studies (8%) used the Wong-Baker scale, 26,27,33 and one study (3%) used a structured interview questionnaire and a subjective pain assessment tool. 8,[12][13][14][15][16][17]19,20,22,24,[26][27][28]30,[32]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,11,14,18,[20][21][22][23][24][25][26][27] In addition, partial and even complete elimination of pain was observed in some patients with longer AVF use. Some patients were so satisfied with the technique that they even asked not to go back to the RL technique.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients were so satisfied with the technique that they even asked not to go back to the RL technique. 7,[9][10][11]14,27 The loss of two accesses (9.5%) due to complications was considered high, as was the occurrence of clots in 47.6% of the patients. However, such intercurrences resulted mainly from the change in cannulator and did not relate to the use of tobacco, contraceptives, and platelet antiaggregating agents, nor to any difficulty in tunnel track formation.…”
Section: Discussionmentioning
confidence: 99%